Comparison of Different Empirical Correlations to Estimate Permeability Coefficient of Quaternary Danube Soils - Pap, Miklós; Mahler, András (Periodica Polytechnica Civil Engineering, 2019)
Permeability coefficient is the most significant soil parameter in seepage calculations. It has been recognized that permeability of granular soils is strongly related to the grain size, thus numerous empirical correlations have been developed to estimate permeability using its grain size characteristics. In this study the empirical correlations proposed by Hazen (1911), Carrier (2003) and Chapuis (2004) are evaluated and compared to laboratory measurement results. Quaternary Danube soils are very typical in the Carpathian basin, thus their permeability is an important question in many geotechnical applications.